The role of traditional Japanese medicine (Kampo) in the practice of psychosomatic medicine: the usefulness of Kampo in the treatment of the stress-related symptoms of women, especially those with peri-menopausal disorder - Ushiroyama, Takahisa (BioMed Central, 2013)
A serious problem currently plaguing the medical field is the widening gap between academic medicine, which studies the features and causes of illness, and the medical care that patients desire. An example of this gap can be observed in the practice of psychotherapy, which is effective only for certain patients. Kampo medicine that combines the advantages of Western medicine with those of traditional Japanese medicine is currently undergoing a revival in the healthcare sector. The therapeutic policies underlying Kampo medicine are based on the physical constitution and current symptoms of each patient. For this reason, Kampo medicine is referred to as “tailor-made medicine” and has properties similar to “mind and body” or psychosomatic medicine. Some women exhibit multiple undefined stress-related symptoms during the peri-menopausal period. In order to accurately diagnose and provide patient-specific treatment, physicians should not only investigate the various stress factors in patients’ lives but should also provide a Sho, or a Kampo diagnosis. The therapeutic approach in Kampo medicine is aimed at harmonizing the mind, body, and spirit; this practice involves the use of narrative and holistic medication that treats the entire being of the patient, resulting in an increased number of specialized treatment plans. There are many Kampo prescriptions tailored to treat women who exhibit various stress-related symptoms. Both Kampo and psychosomatic medicine are based on the principles of narrative-based medicine, and by integrating these two medical systems, an ideal system can be devised to better cope with the various needs of patients. This new medical system established by integrating and harmonizing Western and Eastern medicine can be used for the treatment of women with stress-related symptoms.